The Effect of Fermentation Time in Full Wash and Honey Processing on Arabica Coffee Characteristics - Bevi Lidya; Isnaeni Rahma Wildiani; Muhammad Zikri Ramadhan; Tri Hariyadi (Fluida, 2024)
Fermentation is the key to every post-harvest processing method carried out. Fermentation in coffee also serves to determine the characteristics of the resulting coffee. To bring out the characteristics of coffee, modification of the fermentation process is used by adding lactic acid bacteria which aims to reduce the caffeine and pH levels in coffee. Low pH in coffee can protect coffee beans from another microorganism and give fruity flavour in coffee. This research aims to determine the effect of lactic acid fermentation time on processing with the full wash and honey method on the characteristics of arabica coffee beans. Fermentation is done with time variations of 8, 16, 24, 32, 40, and 48 hours. The post-harvest processing carried out is the full wash and honey method. The analysis was carried out to determine the water content (gravimetric method), caffeine content (UV- Vis spectrophotometry), pH (pH metre), and total acid level (titration method). The results showed that the longer the fermentation time, the lower the caffeine content and pH levels in coffee. Processing with the full wash method produces lower caffeine levels, while the honey method produces a lower pH and a higher total acid content. The best experiment was obtained at 40-hour fermentation using the honey method, with water content of 9.07%; caffeine 1.11%; pH 4.00; and total acid content of 27%, based on SNI 2008.